Evaluation of Vehicle Component Maintenance and Care Strategy using The Reliability Centered Maintenance Method - Fitria Arumning Sukma; Sugianto Sugianto (JTI: Jurnal Teknik Industri, 2026)
This study aims to evaluate the vehicle maintenance strategy at PT XYZ, an intercity bus operator (AKAP) managing a mixed fleet consisting of Hino RK, Hino RM, and Mercedes-Benz units, and to develop an optimized preventive maintenance schedule for critical wheel system components. A quantitative descriptive approach was applied using historical failure data from January 2024 to December 2025 which recorded 1,299 incidents. The Reliability Centered Maintenance (RCM) method was employed by integrating Pareto analysis for critical system identification, Failure Mode and Effects Analysis (FMEA) for risk prioritization, Logic Tree Analysis (LTA) for failure classification, and Mean Time Between Failure (MTBF) calculation to determine maintenance intervals. The wheel system was identified as the most critical system with a contribution of 403 failures or 31.02 percent. FMEA revealed that the Hino RK fleet carries the highest risk, with bearing and wheel hub reaching maximum RPN values of 512 and 504 respectively. Five components were classified as Safety Problems (Category A) and the wheel seal as a Hidden Failure (Category D). MTBF based intervals range from 59 days for the RK fleet tire to 2,693 days for the RK fleet rim, with tire inspection being the most frequent maintenance requirement across all fleet types. Implementation of an RCM based preventive maintenance regime using a Condition Directed (CD) strategy for five detectable components and a Time Directed (TD) strategy for the wheel seal offers a structured transition from the existing reactive system. The findings provide fleet specific maintenance schedules and cost estimates that support reduced unplanned downtime, improved safety compliance, and optimized maintenance expenditure for AKAP bus operators.  Keywords: Bus Maintenance, FMEA, Logic Tree Analysis, MTBF, Reliability Centered Maintenance